2020
DOI: 10.3389/fimmu.2020.608653
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reconstitution After Gene Therapy Approaches in Patients With X-Linked Severe Combined Immunodeficiency Disease

Abstract: X-linked severe immunodeficiency disease (SCID-X1) is an inherited, rare, and life-threating disease. The genetic origin is a defect in the interleukin 2 receptor γ chain (IL2RG) gene and patients are classically characterized by absence of T and NK cells, as well as presence of partially-functional B cells. Without any treatment the disease is usually lethal during the first year of life. The treatment of choice for these patients is hematopoietic stem cell transplantation, with an excellent survival rate (&a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 145 publications
(355 reference statements)
0
21
0
Order By: Relevance
“…Moreover, we found that IL2RG and IL2RB significantly decreased after DAP10 downregulation. Since these two proteins were crucial in the intracellular signaling during the activation process of CD8+ T cells [ 28 , 29 ], we supposed that CD8+ T cells in DAP10 low expression patients could not transmit downstream signals to the nucleus when exposed to the antigen, which led to the blockade of activation of CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that IL2RG and IL2RB significantly decreased after DAP10 downregulation. Since these two proteins were crucial in the intracellular signaling during the activation process of CD8+ T cells [ 28 , 29 ], we supposed that CD8+ T cells in DAP10 low expression patients could not transmit downstream signals to the nucleus when exposed to the antigen, which led to the blockade of activation of CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, patients with genetic mutations of the IL2RG gene are classically characterized by the absence or severe reduction of T and NK cell numbers, as well as the presence of non-functional B cells ( 33 ), these mutations are mainly localized within the exons 3-5 ( 34 , 35 ). Missense mutations are the most common pathogenic changes observed, followed by nonsense variants and insertions/deletions ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…These concerns were highlighted by a gene therapy trial to treat children with X-linked severe combined immunodeficiency. Some of the patients developed acute lymphoblastic T-cell leukemia following gene therapy, due to vector-mediated insertional mutagenesis ( 27 , 28 ). The governance of novel technologies such as designer nucleases, e.g., CRISPR/Cas9 technology, require the development of advanced strategies to identify potential complications such as off-target editing or immunogenicity.…”
Section: Quality Controlmentioning
confidence: 99%